Diet and Genotype of an Aquatic Invertebrate Affect the Composition of Free-Living Microbial Communities - Macke, Emilie; Callens, Martijn; Massol, Francois; Vanoverberghe, Isabel; De Meester, Luc; Decaestecker, Ellen (Frontiers in Microbiology, 2020)
In spite of the growing interest in the role of the gut microbiome (GM) in host physiology and health, the mechanisms governing its assembly and its effects on the environment are poorly understood. In this article, we show that the host genotype and the GM of Daphnia influence the community structure of the surrounding bacterioplankton (BPK). When Daphnia genotypes were placed in an identical environment, both the GM and BPK showed a genotype and diet-dependent taxonomic composition. Overall, the GM strongly differed from the BPK in taxonomic composition and was characterized by a lower α-diversity, suggesting a selective rejecting of bacteria from the regional species pool. In a microbiome transplant experiment, the assembly of both the GM and BPK was strongly affected by the host genotype and the inoculum to which germ-free Daphnia were exposed. The combination of these results suggests a strong interaction between the host genotype, its GM and free-living microbial communities. Currently, it is generally assumed that an animal’s diet has a strong effect on the animal’s GM, but only a negligible (if any) effect on the surrounding environment. However, our results indicate that the diet/microbiome inocula have a small effect on the gut community and a large effect on the community in the surrounding environment. This structuring genotype × microbiome × environment effect is an essential prerequisite that could indicate that microbiomes play an important role in eco-evolutionary processes.